Bazy danych w archiwach państwowych. Podstawy prawne i wykorzystanie praktyczne - Galuba, Rafał (Człowiek i Społeczeństwo, 2013)
On the XX turning point and the 21st century with important process occurring in the sphere of functioning of the civil service, including the state archival service, there is a transformation to the global information society, of which providing the free flow for information is a base in an electronic form. The development of electronic administration and becoming widespread are standing the on-line documentation new challenges in collecting, taking over, protecting and making archival materials available before the state archival service. He/she requires not only a computer development of infrastructure and giving the essential provisions essential for the appropriate circulation to the on-line documentation, but also preparing authors and archivists for assessing (of classifying and classifying) of on-line documentation. New tasks are standing in the sphere of disseminating archive information in an electronic form. Legal grounds for creating, the protection and correct practical functioning of databases at national archives consist of two types of provisions: 1) general, which constitutional bases are regulating you and civil rights, principles of operation of administration and public institutions and the process of the computerization of the public sector; 2) detailed – of archival law which is resolving principles of archival activity. Databases are playing an important role in the computerization of national archives and disseminating archive information amongst citizens. Still they are essential of action in favour of increasing their effectiveness and the public application as part of the realization of the concept of development of the global information society. Otherwise national archives and their users will be ruled out computer, when existing solutions in implementing electronic administration and managing the on-line documentation will remain on the margin of the worldwide process for the computerization.